Experiences of psychology applicants from the Global South: Faculty and student perspectives on how to overcome barriers to inclusive education - Aggarwal, Pankhuri; Ghodke, Nikita; Raval, Vaishali V. (Journal of International Students, 2025)
Although vital to efforts to promote global psychological science, applicants from the Global South continue to experience numerous challenges in securing postbaccalaureate research positions and admission to graduate programs in the Global North. In the present study, international students and applicants (N = 81, Mage = 25.5 years, 82.7% women) from Asia, Africa, and Latin America completed an online survey about their professional experiences prior to pursuing graduate school in the Global North, challenges faced while applying, and strategies for successfully navigating the application process. We also surveyed faculty members (N = 56, Mage = 46.0 years, 67.9% women) in graduate programs in the Global North about their experiences recruiting international applicants in their programs/labs and asked them to provide recommendations to students for successful application outcomes. Inductive content analysis yielded a total of 59 themes across 4 categories. The implications for education and training in psychology are discussed.